The effect of soft tissue therapy for recreational runners with non-specific low back pain - Gawda, Piotr; Dmoszyńska-Graniczka, Magdalena; Rojewski, Robert; Zawadka, Magdalena; Ginszt, Michał (Journal of Education, Health and Sport, 2017)
Background: Many of recreational runners have not practiced running before and for years have lived sedentary lives. Non-specific low back pain may occur in this group of runners during movements of the lumbar spine while running. Aim: Reporting of efficacy and effectiveness of manual therapy in this target group of runners was the aim of this study. Material and methods: The study comprised of 40 recreational runners (29 males, 11 females; mean age: 42±12) training three times a week. In order to check how the training duration affected the results of treatment tree groups were compared: runners training for no longer than one month (A: 8 runners), runners training from 1 to 3 months (B: 12 runners) and runners training for more than 3 months (C: 20 runners). The pain intensity numerical scale (NRS) and finger-floor test were determined before and after therapy, which consists of myofascial release and compression technique. Results: The significant differences in the fingers-floor test and intensity of pain before and after therapy were observed. The results of fingers-floor test decreased from 11.27 to 6.14 after therapy, and pain intensity measured by NRS decreased from 3.75 to 0.94 after therapy. The best treatment effect measured by numerical scale was achieved by runners from group B and the lowest effects in group A. Conclusions: Non-specific low back pain physiotherapy based on soft tissue techniques is statistically highly effective for improve finger-toe flexibility and decrease the intensity of pain.